Conventional and ultrastructural analyses of the chromosomes of Discocyrtus pectinifemur (Opiliones, Laniatores, Gonyleptidae) - Schneider, M. C. [UNESP]; Zacaro, A. A.; Oliveira, R. M. [UNESP]; Gnaspini, P.; Cella, D. M. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Among the Opiliones, species of the suborders Cyphophthalmi, Eupnoi, Dyspnoi and Laniatores have shown very diverse diploid chromosome numbers. However, only certain Eupnoi species exhibit XY/XX and ZZ/ZW sex chromosome systems. Considering the scarcity of karyotypical information and the absence of structurally identifiable sex chromosomes in the suborder Laniatores, we decided to analyse the chromosomes and bivalents of Discocyrtus pectinifemur (Gonyleptidae) to identify possible sex differences. Testicular cells examined under light microscopy showed it high diploid number, 2n = 88, meta/submetacentric chromosome morphology and a nucleolar organizer region on pair 35. Prophase I microspreading observed in transmission electron microscopy exhibited 44 synaptonemal complexes with similar electron density and thickness. The total and regular synapsis between the chromosomes of the bivalents was also noted in pachytene nuclei. Male mitotic and meiotic chromosomes revealed no distinct characteristic that could be related to the occurrence of heteromorphic sex chromosomes. Evolutionary trends of chromosome differentiation in the four suborders of Opiliones are discussed here.
Keywords: chromosomal differentiation; karyotype; meiosis; nucleolar organizer; synaptonemal complex